IMPLEMENTASI SOFTWARE SIBELIUS PADA PEMBELAJARAN TEORI MUSIK - harmony, feritrio; Hadijaya, Christanto; Yosepin, Evo Seyilin (Shift Key : Jurnal Teologi dan Pelayanan, 2022)
AbstractThe use of the Sibelius software media in the music theory course in the music study program at the Christ Alpha Omega Theology High School. From the research that researchers have done, it was found that the method of teaching learning boldly for music theory courses through the Sibelius software is very effective in providing understanding to students, because through this Sibelius media or software students can experience directly auditively and visually so that the presentation of theoretical lecture material music can be understood by students.